Statistical asssessment of phenol biodegradation by a metal-tolerant binary consortium of indigenous Antarctic bacteria - Subramaniam, Kavilasni; Ahmad, Siti Aqlima; Convey, Peter; Shaharuddin, Noor Azmi; Abdul Khalil, Khalilah; Tengku Mazuki, Tengku Athirrah; Gomez Fuentes, Claudio; Zulkharnain, Azham (MDPI AG, 2021)
Since the heroic age of Antarctic exploration, the continent has been pressurized by multiple anthropogenic activities, today including research and tourism, which have led to the emergence of phenol pollution. Natural attenuation rates are very slow in this region due to the harsh environmental conditions; hence, biodegradation of phenol using native bacterial strains is recognized as a sustainable remediation approach. The aim of this study was to analyze the effectiveness of phenol degradation by a binary consortium of Antarctic soil bacteria, Arthrobacter sp. strain AQ5-06, and Arthrobacter sp. strain AQ5-15. Phenol degradation by this co-culture was statistically optimized using response surface methodology (RSM) and tolerance of exposure to different heavy metals was investigated under optimized conditions. Analysis of variance of central composite design (CCD) identified temperature as the most significant factor that affects phenol degradation by this consortium, with the optimum temperature ranging from 12.50 to 13.75 °C. This co-culture was able to degrade up to 1.7 g/L of phenol within seven days and tolerated phenol concentration as high as 1.9 g/L. Investigation of heavy metal tolerance revealed phenol biodegradation by this co-culture was completed in the presence of arsenic (As), aluminum (Al), copper (Cu), zinc (Zn), lead (Pb), cobalt (Co), chromium (Cr), and nickel (Ni) at concentrations of 1.0 ppm, but was inhibited by cadmium (Cd), silver (Ag), and mercury (Hg).